2015
DOI: 10.1007/s13277-015-3923-z
|View full text |Cite
|
Sign up to set email alerts
|

Antisense-miR-21 enhances differentiation/apoptosis and reduces cancer stemness state on anaplastic thyroid cancer

Abstract: Anaplastic thyroid carcinoma (ATC) is the most aggressive malignancy in thyroid cancers. Resistance to current therapies is still a challenge. MicroRNAs are a class of small non-coding RNAs, regulating gene expression. MiR-21 is an oncomiR that is overexpressed in nearly all cancers including ATC. Accumulating evidence suggested that miR-21 has a role in cancer stemness state, apoptosis, cell cycle progression, and differentiation. Therefore, we evaluated the application of Off-miR-21 to sequester the microRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 42 publications
2
36
0
Order By: Relevance
“…MiR-21 has been reported to be upregulated in various cancers, and it inhibited colorectal cancer cell apoptosis and enhanced cell growth. 12,14,29,30 Our experimental data were almost identical to previously reported literature. Furthermore, we found a significant negative correlation between miR-21 and…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…MiR-21 has been reported to be upregulated in various cancers, and it inhibited colorectal cancer cell apoptosis and enhanced cell growth. 12,14,29,30 Our experimental data were almost identical to previously reported literature. Furthermore, we found a significant negative correlation between miR-21 and…”
Section: Discussionsupporting
confidence: 90%
“…The mutation allele of rs6504593 reduced the binding of miR‐21 to the IGF2BP1 3ʹ‐UTR and increased IGF2BP1 expression, which leads to the initiation of colorectal cancer. MiR‐21 has been reported to be upregulated in various cancers, and it inhibited colorectal cancer cell apoptosis and enhanced cell growth . Our experimental data were almost identical to previously reported literature.…”
Section: Discussionsupporting
confidence: 90%
“…To explain these results, targeted mRNAs such as THRB, PTEN and PDCD4 have been reported as repressed. However, the direct inhibition of these mRNAs by miR-21-5p has only been proved in non-thyroid cell lines [8487]. On the other hand, Frezzetti et al [88] performed target and pathway bioinformatics analyses based on the modulated mRNAs following an in vitro increase of miR-21-5p expression in thyroid cells.…”
Section: Physiopathologymentioning
confidence: 99%
“…Moreover miR-21 targets Sprouty2 resulting in cellular protrusions enhancement and augment of cell proliferation and migration [60]. Several studies in vitro have shown that miR-21 influences tumor cell growth and apoptosis [61][62][63][64]. Thus, miR-21 acting as a negative prognostic biomarker has been widely accepted.…”
Section: Discussionmentioning
confidence: 99%